TRANSPORTASI LIGHT RAIL TRANSIT (LRT) PALEMBANG SUMATERA SELATAN BERDAMPAK LINGKUNGAN DAN PENGEMBANGAN USAHA PERKOTAAN SEKTOR NON FARE BOX - Ridho, Muhammad Firman; Buchari, Erika (Universitas Muhammadiyah Palembang, 2023)
Palembang's Light Rail Transit (LRT) rail transportation is a component of the city's rapid transitinitiative which provides 13 stations on the LRT rapid transit line, a catalyst for transit-oriented, highdensity, comparative analysis with other major cities of developed countries that have been successfulimplement this form of mass transit. mixed-use development; economical investment, providing a returnon investment for property owners, businesses and municipalities; and a catalyst for social change,improving health, the environment and community connectivity. LRT revenue comes from fare-box whichcomes from ticket sales and non-fare-box or revenue outside of ticket fares, the four main businesssectors outside of transportation services are advertising, retail, telecommunications, as well as eventsand activation.